2011
DOI: 10.1021/jp1092724
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into the Adsorption of H2S in the Flexible MIL-53(Cr) and Rigid MIL-47(V) MOFs: Infrared Spectroscopy Combined to Molecular Simulations

Abstract: International audienceThe adsorption of the acid gas H2S has been explored in both MIL-47(V) and MIL-53(Cr) porous metal organic frameworks (MOFs) by combining infrared measurements and molecular simulations. It is shown that while the MIL-47(V) structure remains rigid upon H2S adsorption up to a pressure of 1.8 MPa, the MIL-53(Cr) solid initially present in the large pore form (LP) switches to its narrow pore version (NP) at very low pressure before undergoing a second structural transition from the NP to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
137
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 38 publications
11
137
0
Order By: Relevance
“…[39] Structural changes from a large pore to a narrow pore were only observed for MIL-53 (Cr), and identified by a red shift of the n18a aromatic C-H bending mode of the terephthalate linkers. [40] The authors showed that the hydrogen bonding between the hydroxyl groups in Vibrational Spectroscopy 87 MIL-53 and the H 2 S provokes closure of the pore (Figure 7).…”
Section: S Interactionsmentioning
confidence: 99%
“…[39] Structural changes from a large pore to a narrow pore were only observed for MIL-53 (Cr), and identified by a red shift of the n18a aromatic C-H bending mode of the terephthalate linkers. [40] The authors showed that the hydrogen bonding between the hydroxyl groups in Vibrational Spectroscopy 87 MIL-53 and the H 2 S provokes closure of the pore (Figure 7).…”
Section: S Interactionsmentioning
confidence: 99%
“…19 These dramatic shifts in the (S-H) stretch observed on CPO-27-Ni and the change from yellow to dark green of the activated sample upon H 2 S adsorption indicate the involvement of Ni 2+ sites into the adsorption mechanism. The mentioned change in colour is further investigated by Uv-Visible spectroscopy as described in the next section.…”
Section: Vibrational Spectroscopy: Ftir and Ramanmentioning
confidence: 94%
“…38,[44][45][46][47][48][49] Among these studies, those using FTIR spectroscopy are less numerous. [49][50][51][52] Assuredly, spectral band identification is a laborious and tedious task, nonetheless, useful to identify the a) Electronic mail: jmarcos@u-bourgogne.fr role of each component of the structure. Knowing which are the major vibrational modes of a given porous structure is a worth information for guiding the formulation of a theoretical model concerning the flexibility or elasticity of MOFs.…”
Section: Introductionmentioning
confidence: 99%